2019
DOI: 10.3390/photonics6040114
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Function in Pseudophakia: Proximal Miosis Behavior and Optical Influence

Abstract: The pseudophakic eye lacks the ability to produce a refractive change in response to object proximity. Thus, individual anatomical features such as the pupil size play an important role in achieving functional vision levels. In this work, the range of pupil sizes at varying object distance was measured in pseudophakic participants. Furthermore, the impact of the measured values on eye optical quality was investigated using a computer simulation model. A binocular eye-tracker was used to measure the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Because the contact between the iris and the tip of the phacoemulsi cation handle is inevitable, the release of in ammatory mediators can not be ruled out, which is the main reason for the localized change of the pupil after operation. Similarly, Ba-AliS [21] also proposed that the effect of cataract surgery on dark adaptation pupil size and maximum pupil contraction could be observed within 3 weeks after operation, and basically recovered 3 months after operation, which was consistent with the self-limitation of pupil contraction proposed by our study. However, KanellopoulosAnastasiosJohn et al [22] showed statistically signi cant changes in pupil size and shape after cataract surgery, and the average reduction of pupil size was between-11% and-13%, and pupil eccentricity decreased greatly (− 39%).In this study, there is no difference in pupil size between one month after operation and before operation, which requires us to take a longer observation time to determine the long-term changes of pupils.…”
Section: Discussionsupporting
confidence: 91%
“…Because the contact between the iris and the tip of the phacoemulsi cation handle is inevitable, the release of in ammatory mediators can not be ruled out, which is the main reason for the localized change of the pupil after operation. Similarly, Ba-AliS [21] also proposed that the effect of cataract surgery on dark adaptation pupil size and maximum pupil contraction could be observed within 3 weeks after operation, and basically recovered 3 months after operation, which was consistent with the self-limitation of pupil contraction proposed by our study. However, KanellopoulosAnastasiosJohn et al [22] showed statistically signi cant changes in pupil size and shape after cataract surgery, and the average reduction of pupil size was between-11% and-13%, and pupil eccentricity decreased greatly (− 39%).In this study, there is no difference in pupil size between one month after operation and before operation, which requires us to take a longer observation time to determine the long-term changes of pupils.…”
Section: Discussionsupporting
confidence: 91%
“…Differences can be explained by variations in pupil dynamics between methods for measuring visual performance. When measuring distance-corrected visual acuities, pupil diameter has been reported to be reduced by −0.23 mm/D, 18 and then a mean reduction of −0.58 mm can be expected between infinite and 40 cm (2.5 D). However, it has not been demonstrated that this reduction also appears with defocus lenses aimed at varying the vergence of light simulating the condition of approximation of an optotype.…”
Section: Discussionmentioning
confidence: 99%
“…10,23 Second, pupil varies with vergence distance, a mean reduction around 0.5 mm can appear at near versus far distance under photopic conditions. 18,22 This can lead to differences between direct measurements of distance-corrected visual acuities and those obtained with defocus curves. Therefore, visual acuity derived from defocus curves should not be considered as interchangeable with direct measurement of distance-corrected visual acuity at different distances in clinical studies.…”
Section: Discussionmentioning
confidence: 99%